Treatment With a Flavonoid-Rich Fraction of Bergamot Juice Improved Lipopolysaccharide-Induced Periodontitis in Rats - Gugliandolo, Enrico; Fusco, Roberta; D’Amico, Ramona; Peditto, Matteo; Oteri, Giacomo; Di Paola, Rosanna; Cuzzocrea, Salvatore; Navarra, Michele (Frontiers in Pharmacology, 2019)
Objective: in this study, we investigated the effects of a flavonoid-rich fraction of Bergamot juice (BJe) in rats subjected to experimental periodontitis induced by a single intragingival injection of lipopolysaccharides (LPS). Main methods: Periodontitis was induced by a single intragingival injection of 1 μl LPS (10 μg/μl) derived from Salmonella typhimurium in sterile saline solution. The injection was made in the mesolateral side at the interdental papilla between the first and the second molar. Fourteen days after LPS injection, we performed radiographic analyses and then we surgically removed the gingivomucosal tissue surrounding the mandibular first molar for histological, immunohistochemical and molecular analysis. Results: LPS significantly induced oedema, tissue damage and increased neutrophil infiltration. At molecular level, we found increased NF-κB translocation as well as raised both TNF-α and IL-1β expression, other than modulation of apoptosis-associated proteins. Moreover, the increased myeloperoxidase activity was associated with up-regulation of adhesion molecules. Immunohistochemical analysis for nitrotyrosine and poly ADP-ribose displayed an intense staining in the gingivomucosal tissue. Oral administration of BJe for 14 consecutive days reduced tissue injury and several markers of gingival inflammation including nuclear NF-κB translocation, cytokines expression, myeloperoxidase activity and the expression of some adhesion molecules such as ICAM and P-selectin. BJe also decreased both nitrosative stress and PARP positive staining. Moreover, it caused down-regulation of Bax and up-regulation of Bcl-2 expression. Conclusion: our findings demonstrate that BJe improves LPS-induced periodontitis in rats by reducing the typical markers of inflammation, thus suggesting its potential in the treatment of periodontal diseases.